Yesus Memberi Makan Lima Ribu Orang: : Studi Eksegese Terhadap Teks Luk. 9:10-17 - Luturmas, Johanis; Raharusun, Johanis H. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2024)
This article presents an exegetical study of the text of Luk. 9:10-17 which recounts the miracle of Jesus feeding the five thousand. The research aims to uncover the theological, historical, and literary meanings of this pericope. It employs a textual criticism, historical context analysis, literary analysis, linguistic analysis, and the examination of major theological themes. The findings of this study indicate that the miracle of feeding the five thousand holds profound theological significance, including the affirmation of Jesus’s identity as the Messiah. This narrative also depicts a test of faith for the disciples and contains strong symbolism related to the Eucharist. This article provides a deep insight into one of the most well-known miracles of Jesus in the Christian tradition.